The Chemistry and Applications of Sustainable Natural Hair Products - Barve, Kalyani; Dighe, Apurva; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book investigates the relationship between phytoconstituents and properties in specific plants, such as Hibiscus rosa sinesis, Cuscuta reflexa, Citrullus colocynthis, Nardostachys jatamansi and Ocimum gratissimum, that are used in hair care products including shampoos, conditioners, dyes, and oils. It explains the impact of these materials on the growth, structure, appearance, and health of hair. It also explores how the chemistry of certain plants from sustainable sources is exploited for use in hair products and nutraceuticals. Additionally, the authors include information on ingredients used for formulating 'green' hair products that treat common conditions such as canities, dandruff and alopecia.
Hair -- Hair Oil -- Hair Shampoo -- Hair Conditioner -- Hair Colours/Dyes.
Keywords: Chemistry, Technical; Pharmaceutical chemistry; Botany; Industrial Chemistry; Pharmaceutics; Plant Science